Reframing mathematics learning through local culture: A PMRI-based approach to strengthen students’ numeracy literacy in Kudus - Maharani Izzatin; Kartono; Zaenuri; Nuriana Rachmani Dewi (Al-Jabar: Jurnal Pendidikan Matematika, 2025)
Purpose: This study investigates the impact of integrating Kudus local culture within the PMRI (Indonesian Realistic Mathematics Education) framework to enhance students' numeracy literacy and engagement. Method: A quasi-experimental design with a posttest-only control group was implemented in a public junior high school in Kudus, Indonesia. Two seventh-grade classes were randomly selected; the experimental group received PMRI-based instruction enriched with local cultural values, while the control group followed conventional teaching. Data analysis involved normality and homogeneity tests, followed by an independent samples t-test. Findings: Results showed a significant difference between the two groups (t = 2.926, p < 0.05), with the experimental group demonstrating higher numeracy literacy, motivation, and stronger contextual understanding. Significance: The integration of local culture through the PMRI approach bridges abstract mathematical concepts with real-world experience, fostering both conceptual mastery and cultural appreciation. This approach offers a promising model for advancing mathematics education in diverse cultural settings.